Kalimat Aktif dan Kalimat Pasif Bahasa Melayu Tengah Dialek Lembak di Kota Bengkulu - Lestari, Hasanah Multi; Rahayu, Ngudining; Diani, Irma (Jurnal Korpus, 2025)
The Lembak dialect is one of the dialects commonly used by the Lembak people, also known as the Lembak ethnic group, which is part of the larger Bengkulu community. This study aims to describe the function, category, and syntactic role of active and passive sentences in Lembak dialect speech in Bengkulu City. The method used is a qualitative descriptive Data collection techniques in this study were carried out by listening, listening freely in conversation, interviews and recording techniques, namely by recording conversations in Tanjung Agung and Tanjung Jaya Villages, Sungai Serut District, Bengkulu City and interviewing the sources. The analysis steps were carried out in stages: 1) data transcription, 2) data identification, and 3) data classification. The results of the study showed that in active sentences, sentence structures were found with the patterns SPO, SPOKet, KetSPO, SPOPel, SketPO, SPOKetPel, and SPKetO. The syntactic functions found were subjects, predicates, objects, descriptions, and complements. Categories in the Lembak dialect found noun phrases, verb phrases, prepositional phrases, adverbial phrases, adjective phrases, and numeral phrases. The syntactic roles found include actors, actions, sufferers, place, results, time, origin, purpose, participants, actions, recipients, number, things, conditions, and tools. Meanwhile, in passive sentences, sentence structures are found with the patterns SPO, SPOKet, KetSPO, SKetPO, KetSPO, and KetSPOPel. The syntactic functions found include subjects, predicates, objects, descriptions, and complements. The categories that appear include noun phrases, verb phrases, prepositional phrases, adverbial phrases, and adjective phrases. The syntactic roles found include sufferers, actions, actors, place, results, time, tools, and origin. In this study, it was found that in Central Malay Lembak dialect, the active sentence form of the verb is not prefixed or even reduced.